2019
DOI: 10.2174/1874434601913010237
|View full text |Cite
|
Sign up to set email alerts
|

An Interventional Study to Improve Colorectal Cancer Screening Knowledge and Health Perceptions among Jordanians' Average Risk Population

Abstract: Context: Globally, Colorectal Cancer (CRC) is the second most commonly occurring cancer in women and the third most commonly occurring cancer in men. Aims: This study was conducted to investigate the current levels of Jordanians' CRC knowledge and health perceptions; and to test the effects of a health education intervention on them. Settings and Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Students’ knowledge regarding risk factors, symptoms and screenings of different types of cancer improved significantly after the HPC, which is consistent with previous findings (Abuadas & Abuadas, 2020; Alkhasawneh et al., 2017; Ouyang & Hu, 2014). Similarly, a Jordanian study found that the BC educational programme, using various teaching methods, was effective in improving university students’ knowledge regarding BC, its warning signs and risk factors (Alsaraireh & Darawad, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Students’ knowledge regarding risk factors, symptoms and screenings of different types of cancer improved significantly after the HPC, which is consistent with previous findings (Abuadas & Abuadas, 2020; Alkhasawneh et al., 2017; Ouyang & Hu, 2014). Similarly, a Jordanian study found that the BC educational programme, using various teaching methods, was effective in improving university students’ knowledge regarding BC, its warning signs and risk factors (Alsaraireh & Darawad, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…), absence of more than two sessions in educational sessions, and migration during the study. According to a similar study conducted by Abuadas et al .,[ 20 ] 95% confidence interval, power of 90%, with probability of loss of 20% of samples, and using the following formula, the samples were determined 50 for each group.…”
Section: Methodsmentioning
confidence: 99%
“…Many research studies have been conducted to understand the individuals 'CRC health beliefs and their screening practices in a different population (Omran and Ismail, 2010;Christou and Thompson, 2012;Ahmad, 2014;Ahmad et al, 2015;Almadi et al, 2015;Alsanea et al, 2015;Abuadas and Abuadas, 2019;Al-Hajeili et al, 2019). A reliable and valid instrument is necessary to recognize and understand such health beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Screening is essential in the prevention process, as it could reduce the incidence of CRC and increase the likelihood of survival (AmericanCancerSociety, 2018). Despite the effectiveness of CRC screening and the availability of CRC screening tests, overall screening rates are low, and the pace of screening progression is slow (Bidouei et al, 2014;Ferlay et al, 2014;Reyes and Miranda, 2015;Bray et al, 2018;Abuadas and Abuadas, 2019). Several studies were conducted to improve understanding of the barriers that maintain low colorectal cancer screening Editorial Process: Submission:02/15/2021 Acceptance:05/10/2021 rates (Bidouei et al, 2014;Almadi et al, 2015;Reyes and Miranda, 2015;Abuadas et al, 2018;Abuadas and Abuadas, 2019;Al-Hajeili et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation